2020
DOI: 10.1016/j.ijid.2020.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a mass gathering (2018 Commonwealth Games) on emergency department presentations with communicable diseases: A retrospective cohort study

Abstract: To identify the impact of a mass gathering event (MGE) on emergency department (ED) patient presentations with communicable diseases and underpinning syndromic indicators (SIs). Methods: This retrospective observational cohort study was undertaken in one large public teaching hospital ED in Queensland, Australia. Routinely collected ED data for patient presentations with an ICD-10 diagnosis corresponding to a communicable disease were used to compare demographic characteristics, clinical characteristics, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…18 This is of new importance in the context of COVID-19. Public health research and evaluation of MGEs are often reported related to specific events, such as the Commonwealth Games or Olympics, 19,20 or related to specific communicable diseases such as Dengue. 21,22 However, the integration of public health principles for research and evaluation are seldom reported in the literature alongside the biomedical, environmental, and psychosocial domains.…”
Section: Public Healthmentioning
confidence: 99%
“…18 This is of new importance in the context of COVID-19. Public health research and evaluation of MGEs are often reported related to specific events, such as the Commonwealth Games or Olympics, 19,20 or related to specific communicable diseases such as Dengue. 21,22 However, the integration of public health principles for research and evaluation are seldom reported in the literature alongside the biomedical, environmental, and psychosocial domains.…”
Section: Public Healthmentioning
confidence: 99%